Interdependencies between Supply and Demand of Transport: The Evolution of Accessibility within the Lyon Metropolitan Area. - Crozet, Yves; Mercier, Aurélie; Ovtracht, Nicolas; Sapet, Loic (My University, 2013)
More and more metropolitan areas are confronted with the contradiction between urban sprawl and sustainable development expectations. To solve those kinds of problems, municipalities and regional government are implementing various projects like BRT, metro or tramway lines, regional trains etc. As a result, strategies for sustainable accessibility emphasize the key role of public transit (PT) to ensure mobility for the future. But these strategies are generally focused on the central part of cities especially through the development of strong radial PT lines. At the same time, more often in a more discrete manner, a lot of improvements are happening an the road network, namely in suburban areas. Putting the focus on the case study of the Lyon metropolitan area (about 3 000 km2 and more than 1.7 million inhabitants), the second largest metropolitan area in France, the objective of our paper is to illustrate the expected and unexpected effects of road transport supply improvements on transport demand. Using "MOSART" (MOdelling and Simulation of Accessibility to netwoRks and Territories), a digital platform joining a GIS and a transport model, we will present the changes in transport demand for road traffic in relation to a new ring road section in the western part of Lyon. We will start by a presentation of MOSART, followed by some comments about the concept of accessibility, the key role of speed, and the fact that the relationship between speed and density is non-symmetrical. Due to this asymmetry, a new ring road project in the western part of Lyon will instantly change the demand an the whole road network and the job accessibility. Therefore, accessibility maps become a useful tool for "territorial intelligence".
Keywords: Verkehrsplanung; Regionalplanung; Metropolregion; Erreichbarkeit; Verkehrsangebot; Verkehrsnachfrage; Nachhaltige Mobilität; GIS; Geoinformationssystem; Siedlungsstruktur